2010
DOI: 10.1049/el.2010.2517
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of photodarkening in Yb-doped aluminosilicate fibres at elevated temperature

Abstract: Photodarkening behavior in Yb-doped aluminosilicate fibers at elevated temperatures is reported. The fiber was core-pumped at 977 nm and the transmitted powers were monitored at 633 (probe) and 977 nm (pump) simultaneously with ~47% of population inversion of Yb 3+ ions. A saturated photodarkening loss was found, which is inversely proportional to temperature and, at ~573 K, the loss was negligible at the pump wavelength. From the decay curves at different temperatures, we found that the photodarkening involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…In [9] the PD process is found to demand 5 -6 eV in activation energy (E A ) or what correspond to 4 -5 excited Yb ions. In [10] dynamic color center bleaching is found to show 0.07 eV in E A with full recovery of the induced PD for fibers operating at 573 K. The photochemical reaction mechanisms for the active pumped fibers relies on the actual level of pump absorption, temperature, fiber geometry and Yb ion concentration. To distinguish the different mechanisms involved in the PD process it appears therefore advantageous to analyze the bleaching of pre-darkened fibers by annealing as the relaxation reaction hereby only relies on fiber temperature.…”
Section: +mentioning
confidence: 94%
“…In [9] the PD process is found to demand 5 -6 eV in activation energy (E A ) or what correspond to 4 -5 excited Yb ions. In [10] dynamic color center bleaching is found to show 0.07 eV in E A with full recovery of the induced PD for fibers operating at 573 K. The photochemical reaction mechanisms for the active pumped fibers relies on the actual level of pump absorption, temperature, fiber geometry and Yb ion concentration. To distinguish the different mechanisms involved in the PD process it appears therefore advantageous to analyze the bleaching of pre-darkened fibers by annealing as the relaxation reaction hereby only relies on fiber temperature.…”
Section: +mentioning
confidence: 94%
“…However, thermal aspects with Yb-doped fibers (YDFs) cannot be simply overlooked if they operate in highpower regimes because their thermal properties are invariably linked to their long-term reliability as well as their overall efficiency [4][5][6][7][8][9][10][11]. For example, the efficiency of an YDF as a gain medium is dependent on the spectroscopy of Yb 3+ ions that changes with temperature [5][6][7], and, in particular, photo-darkening (PD) effects are significantly affected with temperature [8][9][10][11]. Consequently, thermal characteristics, together with nonlinear scattering characteristics, can eventually be limiting factors to the performance of an YDF [12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, thermal characteristics, together with nonlinear scattering characteristics, can eventually be limiting factors to the performance of an YDF [12][13]. Thus, they have been intensively investigated from various prospects [4][5][6][7][8][9][10][11]. However, most of the related results have been limited to aluminosilicate (Al)-based YDFs [6,7] since they have predominantly been utilized in many high-power applications [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, photodarkening experiments performed at elevated temperatures have shown that photodarkening is accelerated by temperature, but result in a lower level of saturation of the losses. 11,12 In this paper, we report our studies on further improving the analysis of photodarkening. We have investigated the photodarkening kinetics and derived the parameters mostly at temperatures that, for the used measurement durations, are below the activation threshold of thermal bleaching.…”
Section: Introductionmentioning
confidence: 99%